Isoform-specific modulation of the chemical sensitivity of conserved TRPA1 channel in the major honeybee ectoparasitic mite, Tropilaelaps mercedesae. Issue 6 (June 2016) - Dong, Xiaofeng; Kashio, Makiko; Peng, Guangda; Wang, Xinyue; Tominaga, Makoto; Kadowaki, Tatsuhiko
Abstract : We identified and characterized the TRPA1 channel of Tropilaelaps mercedesae (TmTRPA1), one of two major species of honeybee ectoparasitic mite. Three TmTRPA1 isoforms with unique N-terminal sequences were activated by heat, and the isoform highly expressed in the mite's front legs, TmTRPA1b, was also activated by 27 plant-derived compounds including electrophiles. This suggests that the heat- and electrophile-dependent gating mechanisms as nocisensitive TRPA1 channel are well conserved between arthropod species. Intriguingly, one TmTRPA1 isoform, TmTRPA1a, was activated by only six compounds compared with two other isoforms, demonstrating that the N-terminal sequences are critical determinants for the chemical sensitivity. This is the first example of isoform-specific modulation of chemical sensitivity of TRPA1 channel in one species. α-terpineol showed repellent activity towards T. mercedesae in a laboratory assay and repressed T. mercedesae entry for reproduction into the brood cells with fifth instar larvae in hives. Thus, α-terpineol could be used as the potential compound to control two major honeybee ectoparasitic mites, T. mercedesae and Varroa destructor, in the apiculture industry.